THE PRESUMPTION OF HARM IN EU PRIVATE ENFORCEMENT OF COMPETITION LAW : EFFECTIVENESS VS OVERCOMPENSATION (EU and comparative law issues and challenges series (ECLIC), 2021)
The main issue that is still disrupting private enforcement of competition law is the calculation of damages. The 2014 Damages Directive contains some alleviations. Particularly Article 17(2) Damages Directive foresees a rebuttable presumption that cartels cause harm. Despite the clear statement in Recital 47 Damages Directive that this presumption should not cover the concrete amount of harm and studies that vary significantly regarding the typical overcharge, some Member States have created presumptions related to the amount of harm. Other Member States want to expand the presumption to non-cartel violations. This article takes a comparative analysis of the different Member States approaches and attempts to test the Damages Directive and EU competition law boundaries more generally. The article takes a sceptical perspective on some of the Member States’ approaches and proposes other solutions to ease the predicaments of damage quantifications: (i) a focus on illicit gains, (ii) amending the calculation guidelines and create a EU-wide competition damages database, (iii) create further procedural measures, such as collective redress instruments, special legal venues for private enforcement of competition law and expert judges, and (iv) foster further party-led solutions.